Tunable Compact Narrow Band THz Sources for Frequency Domain THz Anisotropic Spectroscopy - George, D. K.; LaFave, T. J.; Markelz, A. G.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P. (Conference on Next-Generation Spectroscopic Technologies XII, 2019)
We demonstrate frequency domain THz anisotropy signature detection for protein crystal models using newly developed compact tunable narrow band THz sources based on Orientation Patterned Gallium Phosphide for turn-key spectroscopic systems.
ISI Document Delivery No.: BN5PJ Times Cited: 0 Cited Reference Count: 17 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Chen JY, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2748852 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Lee Y. S., 2006, APPL PHYS LETT, V89 Lee YS, 2000, APPL PHYS LETT, V76, P2505, DOI 10.1063/1.126390 Lin A., 2013, ANTIPHASE DOMAIN ANN Niessen K. A., BIOPHYSICAL J, V112, P933 Niessen KA, 2019, NAT COMMUN, V10, DOI 10.1038/s41467-019-08926-3 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 PARSONS DF, 1971, APPL OPTICS, V10, P1683 Singh R., 2013, PHYSICS Strachan CJ, 2005, J PHARM SCI-US, V94, P837, DOI 10.1002/jps.20281 Tassev V., 2013, SPIE LASE, V9 Tekavec P., 2017, FRONTIERS OPTICS 201 Tonouchi M, 2007, NAT PHOTONICS, V1, P97, DOI 10.1038/nphoton.2007.3 Walther M, 2003, CHEM PHYS, V288, P261, DOI 10.1016/S0301-0104(03)00031-4 Zeitler JA, 2009, EUR J PHARM BIOPHARM, V71, P2, DOI 10.1016/j.ejpb.2008.08.012 George, D. K. LaFave, T. J. Markelz, A. G. Mcnee, Ian Tekavec, Patrick Kozlov, Vladimir Schunemann, Peter LaFave, Tim/0000-0003-2925-8657 NATIONAL INSTITUTE OF GENERAL MEDICAL SCIENCESUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R41GM125486] Funding Source: NIH RePORTER; NIGMS NIH HHSUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R41 GM125486] Funding Source: Medline 0277-786x 1098311
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation

Tunable narrow band sources for anisotropic THz spectroscopy - George, D. K.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P.; Markelz, A. G. (APS S23-002, 2019)

Tunable narrowband THz generation in orientation patterned gallium phosphide for THz anisotropy identification - McNee, I.; Tekavec, P.; Kozlov, V.; Markelz, A. G.; George, D. K.; Schunemann, P. (Nonlinear Frequency Generation and Conversion: Materials and Devices Xviii, 2019)
We demonstrate tunable narrowband THz generation by optical rectification of a femtosecond pulse in Orientation Patterned Gallium Phosphide. Center frequencies of 0.9 - 3.8 THz with average power up to 15 mu W were achieved using a 1.064 mu m fiber laser for the pump laser. Biomolecular characterization for an early application of this system is also shown in this work by anisotropic spectroscopic signature detection of molecular crystals in the THz region.
ISI Document Delivery No.: BM9XB Times Cited: 2 Cited Reference Count: 8 Cited References: Fejer M. M., 2013, ANTIPHASE DOMAIN ANN, P258 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Lee YS, 2000, APPL PHYS LETT, V76, P2505, DOI 10.1063/1.126390 Niessen K. A., BIOPHYSICAL J, V112, P933 PARSONS DF, 1971, APPL OPTICS, V10, P1683 Singh R., 2013, MODULATED ORIENTATIO Tassev V., 2013, SPIE LASE, P9 Tekavec P., 2017, FRONTIERS OPTICS 201 McNee, Ian Tekavec, Patrick Kozlov, Vladimir Markelz, A. G. George, D. K. Schunemann, Peter Proceedings Paper Conference on Nonlinear Frequency Generation and Conversion - Materials and Devices XVIII Feb 05-07, 2019 San Francisco, CA Spie 1000 20th st, po box 10, bellingham, wa 98227-0010 usa 0277-786x Unsp 1090218
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation

THz Anisotropy Identification using Tunable Compact Narrow Band THz Sources - George, D. K.; Markelz, A. G.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P. (2018 43rd International Conference on Infrared, Millimeter, and Terahertz Waves, 2018)
We demonstrate THz anisotropy signature determination of a protein crystal model using newly developed compact tunable narrow band THz sources for turn-key spectroscopic systems for the bio molecular community.
ISI Document Delivery No.: BL3GO Times Cited: 0 Cited Reference Count: 6 Cited References: Dhillon SS, 2017, J PHYS D APPL PHYS, V50, DOI 10.1088/1361-6463/50/4/043001 Lee YS, 2000, APPL PHYS LETT, V76, P2505, DOI 10.1063/1.126390 Lin A., 2013, ANTIPHASE DOMAIN ANN, P258 Niessen KA, 2017, BIOPHYS J, V112, P933, DOI 10.1016/j.bpj.2016.12.049 Tassev V., 2013, SPIE LASE, P9 Tekavec P., 2017, FRONTIERS OPTICS 201 George, D. K. Markelz, A. G. Mcnee, Ian Tekavec, Patrick Kozlov, Vladimir Schunemann, Peter Irmmw-thz Proceedings Paper 43rd International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) Sep 09-14, 2018 Nagoya, JAPAN IEEE Microwave Theory & Tech Soc, TeraTech, JSPS, JSIR, Japan Soc Appl Phys, IEEJ, CSJ, AIP, APL Photon, AIP, Journal Appl Phys, EiC, SPSJ, Terahertz Syst Consortium, AICHI, Nagoya Convent & Visitors Bur, ADVANTEST CORP, AmTechs Corp, Menlo Systems GmbH, Nippo Precigion Co Ltd, TeraMetrix LLC Div Luna, ATN Japan LTD, DAHENG NEW EPOCH TECHNOL INC, FEMTO Dev Inc, KYOWA FINTECH Co Ltd, Spectra Design Ltd, TeraView Ltd, TYDEX LLC, Virginia Diodes Inc, PNP, Tydex Res & Ind Opt, Femtowave, Kyowa Fine Tech Co Ltd, Daheng Opt 345 e 47th st, new york, ny 10017 usa 2162-2027

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
ISI Document Delivery No.: EI0HL Times Cited: 541 Cited Reference Count: 209 Cited References: Adam AJL, 2011, J INFRARED MILLIM TE, V32, P976, DOI 10.1007/s10762-011-9809-2 Ahmed SS, 2012, IEEE MICROW MAG, V13, P26, DOI 10.1109/MMM.2012.2205772 Alliance N., 2015, CISC VIS NETW IND GL, P1 [Anonymous], 2013, 178512012 IEEE [Anonymous], 2014, IEEE T ELECT DEVICES, V61 [Anonymous], 2012, 178522016 IEEE [Anonymous], 2015, P17852 IEEE Appleby R, 2015, P SOC PHOTO-OPT INS, V9462 Arnone DD, 1999, PROC SPIE, V3828, P209, DOI 10.1117/12.361037 Ashworth PC, 2009, OPT EXPRESS, V17, P12444, DOI 10.1364/OE.17.012444 AUSTON DH, 1988, IEEE J QUANTUM ELECT, V24, P184, DOI 10.1109/3.114 Barbieri S, 2011, NAT PHOTONICS, V5, P306, DOI [10.1038/NPHOTON.2011.49, 10.1038/nphoton.2011.49] Barker RJ., 2005, MODERN MICROWAVE MIL Basov DN, 2011, REV MOD PHYS, V83, P471, DOI 10.1103/RevModPhys.83.471 Bauwens M. F., 2014, P IEEEMTT S INT MICR, P1, DOI [10.1109/MWSYM.2014.68486 07, DOI 10.1109/MWSYM.2014.6848607] Beard MC, 2002, NANO LETT, V2, P983, DOI 10.1021/nl0256210 Beard MC, 2000, PHYS REV B, V62, P15764, DOI 10.1103/PhysRevB.62.15764 Bechtel HA, 2014, P NATL ACAD SCI USA, V111, P7191, DOI 10.1073/pnas.1400502111 Belkin MA, 2008, OPT EXPRESS, V16, P3242, DOI 10.1364/OE.16.003242 Belkin MA, 2015, PHYS SCRIPTA, V90, DOI 10.1088/0031-8949/90/11/118002 Bell R., 2012, INTRO FOURIER TRANSF Berry CW, 2013, NAT COMMUN, V4, DOI 10.1038/ncomms2638 Blanchard F, 2011, OPT EXPRESS, V19, P8277, DOI 10.1364/OE.19.008277 Blau J, 2013, P FREE EL LAS FEL 20, P486 Booske JH, 2011, IEEE T THZ SCI TECHN, V1, P54, DOI 10.1109/TTHZ.2011.2151610 Booske JH, 2008, PHYS PLASMAS, V15, DOI 10.1063/1.2838240 Boppel S, 2012, 2012 IEEE 12TH TOPICAL MEETING ON SILICON MONOLITHIC INTEGRATED CIRCUITS IN RF SYSTEMS (SIRF), P77, DOI 10.1109/SiRF.2012.6160142 Burghoff D, 2014, NAT PHOTONICS, V8, P462, DOI 10.1038/nphoton.2014.85 Busch SF, 2014, J INFRARED MILLIM TE, V35, P993, DOI 10.1007/s10762-014-0113-9 Byrne MB, 2011, APPL PHYS LETT, V98, DOI 10.1063/1.3579258 Carr GL, 2002, NATURE, V420, P153, DOI 10.1038/nature01175 Carranza IE, 2015, IEEE T THZ SCI TECHN, V5, P892, DOI 10.1109/TTHZ.2015.2463673 Castro-Camus E, 2007, OPT EXPRESS, V15, P7047, DOI 10.1364/OE.15.007047 Chan WL, 2007, REP PROG PHYS, V70, P1325, DOI 10.1088/0034-4885/70/8/R02 Chattopadhyay G, 2011, IEEE T THZ SCI TECHN, V1, P33, DOI 10.1109/TTHZ.2011.2159561 Chen HT, 2003, APPL PHYS LETT, V83, P3009, DOI 10.1063/1.1616668 Chen JN, 2012, NATURE, V487, P77, DOI 10.1038/nature11254 Cocker T L, 2016, J PHYS D, V16, P1421 Cocker TL, 2013, NAT PHOTONICS, V7, P620, DOI [10.1038/NPHOTON.2013.151, 10.1038/nphoton.2013.151] Coleman B, 2001, Issue Brief (Public Policy Inst (Am Assoc Retired Pers)), P1 Cooper KB, 2014, IEEE MICROW MAG, V15, P51, DOI 10.1109/MMM.2014.2356092 Cruz F C, 2007, C MICR OPT Cunningham J, 2010, ELECTRON LETT, V46, pS34, DOI 10.1049/el.2010.3317 Dean P, 2011, OPT LETT, V36, P2587, DOI 10.1364/OL.36.002587 Dietz RJB, 2014, OPT LETT, V39, P6482, DOI 10.1364/OL.39.006482 Dietz RJB, 2014, OPT EXPRESS, V22, P19411, DOI 10.1364/OE.22.019411 Dobrovolsky V, 2007, SEMICOND SCI TECH, V22, P103, DOI 10.1088/0268-1242/22/2/017 Ducournau G, 2014, IEEE T THZ SCI TECHN, V4, P328, DOI 10.1109/TTHZ.2014.2309006 Dunsmore J.P., 2012, HDB MICROWAVE COMPON Duvillaret L, 1999, APPL OPTICS, V38, P409, DOI 10.1364/AO.38.000409 Eisele M, 2014, NAT PHOTONICS, V8, P841, DOI [10.1038/nphoton.2014.225, 10.1038/NPHOTON.2014.225] Falconer RJ, 2012, J INFRARED MILLIM TE, V33, P973, DOI 10.1007/s10762-012-9915-9 Fathololoumi S, 2012, OPT EXPRESS, V20, P3866, DOI 10.1364/OE.20.003866 Fausti D, 2011, SCIENCE, V331, P189, DOI 10.1126/science.1197294 Federici J, 2010, J APPL PHYS, V107, DOI 10.1063/1.3386413 Fei Z, 2012, NATURE, V487, P82, DOI 10.1038/nature11253 FETTERMAN HR, 1974, APPL PHYS LETT, V24, P70, DOI 10.1063/1.1655098 Freeman JR, 2013, OPT EXPRESS, V21, P16162, DOI 10.1364/OE.21.016162 Frisk U, 2003, ASTRON ASTROPHYS, V402, pL27, DOI 10.1051/0004-6361:20030335 Garet F, 2014, APPL PHYS LETT, V105, DOI 10.1063/1.4890732 Gavrilov NG, 2007, NUCL INSTRUM METH A, V575, P54, DOI 10.1016/j.nima.2007.01.023 Gensch M., 2013, P 35 INT FREE EL LAS, P474 George DK, 2012, J OPT SOC AM B, V29, P1406, DOI 10.1364/JOSAB.29.001406 Giliberti V, 2013, APPL PHYS LETT, V103, DOI 10.1063/1.4819734 Grant J, 2013, LASER PHOTONICS REV, V7, P1043, DOI 10.1002/lpor.201300087 Green B, 2016, SCI REP-UK, V6, DOI 10.1038/srep22256 Griffith P.R., 2007, FOURIER TRANSFORM IN GRISCHKOWSKY D, 1990, J OPT SOC AM B, V7, P2006, DOI 10.1364/JOSAB.7.002006 Gruene P, 2008, SCIENCE, V321, P674, DOI 10.1126/science.1161166 Han NR, 2014, OPT LETT, V39, P3480, DOI 10.1364/OL.39.003480 Han RN, 2013, IEEE J SOLID-ST CIRC, V48, P2296, DOI 10.1109/JSSC.2013.2269856 Hanham SM, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4927242 Hassel J, 2015, PROC SPIE, V9651, DOI 10.1117/12.2197522 Hauri CP, 2011, APPL PHYS LETT, V99, DOI 10.1063/1.3655331 He W, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4932099 Hebling J, 2002, OPT EXPRESS, V10, P1161, DOI 10.1364/OE.10.001161 Heinz E, 2015, J INFRARED MILLIM TE, V36, P879, DOI 10.1007/s10762-015-0170-8 Henry SC, 2012, OPT ENG, V51, DOI 10.1117/1.OE.51.9.091603 Hesler J L, 2006, P 7 INT S SPAC TER T, P215 Hintzsche H, 2012, CRIT REV ENV SCI TEC, V42, P2408, DOI 10.1080/10643389.2011.574206 Hishida M, 2011, PHYS REV LETT, V106, DOI 10.1103/PhysRevLett.106.158102 Ho IC, 2010, OPT EXPRESS, V18, P2872, DOI 10.1364/OE.18.002872 HU BB, 1995, OPT LETT, V20, P1716, DOI 10.1364/OL.20.001716 Huang C, 2012, PHYS REV B, V85 Huber R, 2001, NATURE, V414, P286, DOI 10.1038/35104522 Jankowiak A., 2013, Synchrotron Radiation News, V26, P22, DOI 10.1080/08940886.2013.791212 Jepsen PU, 2007, CHEM PHYS LETT, V442, P275, DOI 10.1016/j.cplett.2007.05.112 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Jepsen PU, 2005, OPT LETT, V30, P29, DOI 10.1364/OL.30.000029 JUICE-Jupiter Icy Moons Explorer, 2014, SRE20141 JUICE EUR S, P1 Kallfass I, 2011, IEEE T THZ SCI TECHN, V1, P477, DOI 10.1109/TTHZ.2011.2160021 Kampfrath T, 2013, NAT PHOTONICS, V7, P680, DOI [10.1038/nphoton.2013.184, 10.1038/NPHOTON.2013.184] Kan T, 2015, NAT COMMUN, V6, DOI 10.1038/ncomms9422 Karpowicz N, 2008, APPL PHYS LETT, V92, DOI 10.1063/1.2828709 Kehr SC, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.256403 Kemp MC, 2011, IEEE T THZ SCI TECHN, V1, P282, DOI 10.1109/TTHZ.2011.2159647 Khalid A, 2014, J APPL PHYS, V115, DOI 10.1063/1.4868705 Kirley MP, 2015, IEEE T THZ SCI TECHN, V5, P1012, DOI 10.1109/TTHZ.2015.2468074 Kiwa T, 2003, OPT LETT, V28, P2058, DOI 10.1364/OL.28.002058 Koch M, 2001, NATO SCI SER II MATH, V27, P241 Koenig S, 2013, NAT PHOTONICS, V7, P977, DOI [10.1038/nphoton.2013.275, 10.1038/NPHOTON.2013.275] Kohler R, 2002, NATURE, V417, P156, DOI 10.1038/417156a Koppens FHL, 2014, NAT NANOTECHNOL, V9, P780, DOI [10.1038/nnano.2014.215, 10.1038/NNANO.2014.215] Kosarev A, 2010, SOLID STATE ELECTRON, V54, P417, DOI 10.1016/j.sse.2009.12.032 Kundu I, 2014, OPT EXPRESS, V22, P16595, DOI 10.1364/OE.22.016595 Kuznetsov SA, 2010, KEY ENG MATER, V437, P276, DOI 10.4028/www.scientific.net/KEM.437.276 Langevin Y, 2005, PAYLOAD MISSION DEFI LaRue JL, 2015, PHYS REV LETT, V115, DOI 10.1103/PhysRevLett.115.036103 Leitenstorfer A, 2014, NEW J PHYS, V16, DOI 10.1088/1367-2630/16/4/045016 Leitner DM, 2006, INT REV PHYS CHEM, V25, P553, DOI 10.1080/01442350600862117 Li LH, 2014, ELECTRON LETT, V50, P309, DOI 10.1049/el.2013.4035 Liu L, 2010, IEEE MICROW WIREL CO, V20, P504, DOI 10.1109/LMWC.2010.2055553 Liu SC, 2016, OPT EXPRESS, V24, P2728, DOI 10.1364/OE.24.002728 Lu X H, 2008, P SOC PHOTO-OPT INS, V7277 Luukanen A, 2003, APPL PHYS LETT, V82, P3970, DOI 10.1063/1.1579562 Mann C, 2009, P SOC PHOTO-OPT INS, V7311, P3970 Mickan S, 2004, PROC SPIE, V5277, P54, DOI 10.1117/12.530386 Mineo M, 2010, IEEE T ELECTRON DEV, V57, P3169, DOI 10.1109/TED.2010.2071876 Mittleman DM, 1996, IEEE J SEL TOP QUANT, V2, P679, DOI 10.1109/2944.571768 Mittleman DM, 1999, APPL PHYS B-LASERS O, V68, P1085, DOI 10.1007/s003400050750 Moon K, 2012, APPL PHYS LETT, V101, DOI 10.1063/1.4733475 Muller AS, 2010, REV ACCEL SCI TECH, V3, P165, DOI 10.1142/S1793626810000427 Muller R, 2015, J INFRARED MILLIM TE, V36, P654, DOI 10.1007/s10762-015-0163-7 Naftaly M, 2015, TERAHERTZ METROLOGY, P1 Nagai M, 2015, OPT EXPRESS, V23, P4641, DOI 10.1364/OE.23.004641 Nagatsuma T, 2012, OPT EXPRESS, V21, P477 Nagel M, 2002, APPL PHYS LETT, V80, P154, DOI 10.1063/1.1428619 Navarro-Cia M, 2015, J INFRARED MILLIM TE, V36, P542, DOI 10.1007/s10762-015-0157-5 Nielsen K, 2009, OPT EXPRESS, V17, P8592, DOI 10.1364/OE.17.008592 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 Nordquist CD, 2011, IEEE J SEL TOP QUANT, V17, P130, DOI 10.1109/JSTQE.2010.2049095 Oh SJ, 2012, J INFRARED MILLIM TE, V33, P74, DOI 10.1007/s10762-011-9847-9 Ojefors E, 2009, IEEE J SOLID-ST CIRC, V44, P1968, DOI 10.1109/JSSC.2009.2021911 Ortolani M, 2008, PHYS REV LETT, V97 Ozerov M, 2014, PHYS REV LETT, V113, DOI 10.1103/PhysRevLett.113.157205 Paoloni C, 2013, IEEE T ELECTRON DEV, V60, P1236, DOI 10.1109/TED.2013.2240686 Parrott EPJ, 2015, APPL SPECTROSC, V69, P1, DOI 10.1366/14-07707 Patrashin M, 2015, IEEE T ELECTRON DEV, V62, P1068, DOI 10.1109/TED.2015.2393358 Peiponen K. E., 2013, TERAHERTZ SPECTROSCO, V171 Peng K, 2015, NANO LETT, V15, P206, DOI 10.1021/nl5033843 Pickwell E, 2004, APPL PHYS LETT, V84, P2190, DOI 10.1063/1.1688448 Ponnampalam L, 2011, J LIGHTWAVE TECHNOL, V29, P2229, DOI 10.1109/JLT.2011.2158186 Pupeza I, 2007, OPT EXPRESS, V15, P4335, DOI 10.1364/OE.15.004335 Rauter P, 2015, LASER PHOTONICS REV, V9, P452, DOI 10.1002/lpor.201500095 Reid CB, 2011, PHYS MED BIOL, V56, P4333, DOI 10.1088/0031-9155/56/14/008 Reid J R, 2012, IEEE 12 TOP M SIL MO, P17 Rosch M, 2015, NAT PHOTONICS, V9, P42, DOI [10.1038/nphoton.2014.279, 10.1038/NPHOTON.2014.279] Rudd JV, 2000, PROC SPIE, V3934, P27, DOI 10.1117/12.386344 Rymanov V, 2015, PHOTONICS, V2, DOI 10.3390/photonics2041152 SANTOS Daisy Conceicao, 2014, THESIS Scherger B, 2011, APPL OPTICS, V50, P2256, DOI 10.1364/AO.50.002256 Schleicher JM, 2009, J APPL PHYS, V105, DOI 10.1063/1.3133093 Schumann S, 2012, OPT EXPRESS, V20, P19200, DOI 10.1364/OE.20.019200 Seeds AJ, 2015, J LIGHTWAVE TECHNOL, V33, P579, DOI 10.1109/JLT.2014.2355137 Sell A, 2008, OPT LETT, V33, P2767, DOI 10.1364/OL.33.002767 Shams H, 2015, IEEE PHOTONICS J, V7, DOI 10.1109/JPHOT.2015.2438437 Shams H, 2014, OPT EXPRESS, V22, P23465, DOI 10.1364/OE.22.023465 Shen YC, 2004, APPL PHYS LETT, V85, P164, DOI 10.1063/1.1768313 Simoens F., 2014, PHILOS T A, V372, P1 Simoens F, 2011, 36 INT C INFR MILL T, P1 Singh A, 2015, OPT EXPRESS, V23, P6656, DOI 10.1364/OE.23.006656 Sirtori C, 2013, NAT PHOTONICS, V7, P691, DOI [10.1038/NPHOTON.2013.208, 10.1038/nphoton.2013.208] SMITH PR, 1988, IEEE J QUANTUM ELECT, V24, P255, DOI 10.1109/3.121 Son JH, 2013, NANOTECHNOLOGY, V24, DOI 10.1088/0957-4484/24/21/214001 Swinyard B, 2013, SPIE SENSORS SYSTEMS Sy S, 2010, PHYS MED BIOL, V55, P7587, DOI 10.1088/0031-9155/55/24/013 Taylor ZD, 2015, IEEE T THZ SCI TECHN, V5, P184, DOI 10.1109/TTHZ.2015.2392628 Teppati V, 2013, CAMB RF MICROW ENG, P1, DOI 10.1017/CBO9781139567626 Tewari P, 2012, P SPIE, V8261 Thomas B., 2014, P 39 INT C INFR MILL, P1 Thumm M, 2014, KIT SCI REPORTS, V7693 Tonouchi M, 2007, NAT PHOTONICS, V1, P97, DOI 10.1038/nphoton.2007.3 Truong BCQ, 2015, IEEE T BIO-MED ENG, V62, P699, DOI 10.1109/TBME.2014.2364025 Turcinkova D, 2015, APPL PHYS LETT, V106, DOI 10.1063/1.4916653 Turner GM, 2002, J PHYS CHEM B, V106, P11716, DOI 10.1021/jp025844e van der Valk NCJ, 2002, APPL PHYS LETT, V81, P1558, DOI 10.1063/1.1503404 van Dijk F, 2014, IEEE PHOTONIC TECH L, V26, P965, DOI 10.1109/LPT.2014.2309353 Vicario C, 2014, PHYS REV LETT, V112, DOI 10.1103/PhysRevLett.112.213901 Vinh NQ, 2015, J CHEM PHYS, V142, DOI 10.1063/1.4918708 Vitiello MS, 2012, NAT PHOTONICS, V6, P525, DOI 10.1038/nphoton.2012.145 Vitiello MS, 2015, OPT EXPRESS, V23, P5167, DOI 10.1364/OE.23.005167 Vitiello MS, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms6884 Wade A, 2009, NAT PHOTONICS, V3, P41, DOI 10.1038/NPHOTON.2008.251 Wallace B., 2015, SPIE NEWSROOM, DOI [10.1117/2.1201503.005871, DOI 10.1117/2.1201503.005871] Wallace VP, 2004, BRIT J DERMATOL, V151, P424, DOI 10.1111/j.1365-2133.2004.06129.x Wang FH, 2015, OPTICA, V2, P944, DOI 10.1364/OPTICA.2.000944 Weightman P, 2012, PHYS BIOL, V9, DOI 10.1088/1478-3975/9/5/053001 Wienold M, 2014, OPT EXPRESS, V22, P3334, DOI 10.1364/OE.22.003334 Wilk R, 2007, C LAS EL BALT MD Williams BS, 2006, ELECTRON LETT, V42, P89, DOI 10.1049/el:20063921 Williams GP, 2006, REP PROG PHYS, V69, P301, DOI 10.1088/0034-4885/69/2/R01 Williams GP, 2008, NAT PHYS, V4, P356, DOI 10.1038/nphys958 Williams MRC, 2013, J PHYS CHEM B, V117, P10444, DOI 10.1021/jp406730a Williams R, 2013, PHYS MED BIOL, V58, P373, DOI 10.1088/0031-9155/58/2/373 Withayachumnankul W, 2008, J OPT SOC AM B, V25, P1059, DOI 10.1364/JOSAB.25.001059 Woerner M, 2013, NEW J PHYS, V15, DOI 10.1088/1367-2630/15/2/025039 Woodward RM, 2003, J INVEST DERMATOL, V120, P72, DOI 10.1046/j.1523-1747.2003.12013.x Wu X, OPT LETT, V39, P5403 Wu ZR, 2013, REV SCI INSTRUM, V84, DOI 10.1063/1.4790427 Xu J, 2003, PROC SPIE, V5268, P19, DOI 10.1117/12.518533 Yamashita M, 2011, OPT EXPRESS, V19, P10864, DOI 10.1364/OE.19.010864 Yan F, 2013, J INFRARED MILLIM TE, V34, P489, DOI 10.1007/s10762-013-0005-4 Yang SH, 2014, IEEE T THZ SCI TECHN, V4, P575, DOI 10.1109/TTHZ.2014.2342505 Yeh KL, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2734374 Zamora A, 2015, IEEE MTT S INT MICR Zhao JF, 2011, IEEE T ELECTRON DEV, V58, P1221, DOI 10.1109/TED.2011.2109723 Zheludev NI, 2012, NAT MATER, V11, P917, DOI [10.1038/NMAT3431, 10.1038/nmat3431] Zhou Y, 2010, PROG ELECTROMAGN RES, V105, P71, DOI 10.2528/PIER10041806 Zibik EA, 2009, NAT MATER, V8, P803, DOI [10.1038/nmat2511, 10.1038/NMAT2511] Dhillon, S. S. Vitiello, M. S. Linfield, E. H. Davies, A. G. Hoffmann, Matthias C. Booske, John Paoloni, Claudio Gensch, M. Weightman, P. Williams, G. P. Castro-Camus, E. Cumming, D. R. S. Simoens, F. Escorcia-Carranza, I. Grant, J. Lucyszyn, Stepan Kuwata-Gonokami, Makoto Konishi, Kuniaki Koch, Martin Schmuttenmaer, Charles A. Cocker, Tyler L. Huber, Rupert Markelz, A. G. Taylor, Z. D. Wallace, Vincent P. Zeitler, J. Axel Sibik, Juraj Korter, Timothy M. Ellison, B. Rea, S. Goldsmith, P. Cooper, Ken B. Appleby, Roger Pardo, D. Huggard, P. G. Krozer, V. Shams, Haymen Fice, Martyn Renaud, Cyril Seeds, Alwyn Stoehr, Andreas Naftaly, Mira Ridler, Nick Clarke, Roland Cunningham, John E. Johnston, Michael B. Huggard, Peter/U-2150-2019; Konishi, Kuniaki/AAN-3624-2020; Zeitler, J. Axel/B-4885-2008; Paoloni, Claudio/AAH-9824-2019; Hoffmann, Matthias C./N-1082-2019; Wallace, Vincent P/A-9320-2012; Johnston, Michael/B-9813-2008; Castro-Camus, Enrique/V-6861-2019; Krozer, Viktor/P-5623-2014; Hoffmann, Matthias C/B-3893-2009; PAOLONI, CLAUDIO/AAA-3211-2020; Gonokami, Makoto/F-3641-2012; Shams, Haymen/H-3754-2012; Ridler, Nick/AAN-9637-2020; Huber, Rupert/N-4126-2018 Konishi, Kuniaki/0000-0003-2389-9787; Zeitler, J. Axel/0000-0002-4958-0582; Hoffmann, Matthias C./0000-0002-3596-9853; Wallace, Vincent P/0000-0003-3814-5400; Johnston, Michael/0000-0002-0301-8033; Krozer, Viktor/0000-0002-2387-1947; Hoffmann, Matthias C/0000-0002-3596-9853; PAOLONI, CLAUDIO/0000-0002-0265-0862; Shams, Haymen/0000-0002-5333-6478; Huber, Rupert/0000-0001-6617-9283; Davies, Alexander/0000-0002-1987-4846; Seeds, Alwyn/0000-0002-5228-627X; Castro-Camus, Enrique/0000-0002-8218-9155; Cunningham, John/0000-0002-1805-9743; Naftaly, Mira/0000-0002-0671-822X; Cumming, David/0000-0002-7838-8362 Engineering and Physical Sciences Research CouncilUK Research & Innovation (UKRI)Engineering & Physical Sciences Research Council (EPSRC) [EP/P015883/1, EP/M00306X/1, EP/K023349/1, EP/M017095/1, EP/L026597/1, EP/J017671/1] Funding Source: researchfish; Natural Environment Research CouncilUK Research & Innovation (UKRI)NERC Natural Environment Research Council [NER/Z/S/2003/00642, NE/L012375/1, NER/Z/S/2000/01292] Funding Source: researchfish; Science and Technology Facilities CouncilUK Research & Innovation (UKRI)Science & Technology Facilities Council (STFC) [ST/P002056/1] Funding Source: researchfish; Direct For Biological SciencesNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Biological InfrastructureNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Molecular and Cellular BioscienceNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1616529] Funding Source: National Science Foundation 566 30 462 Iop publishing ltd Bristol 1361-6463
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Measuring phonons in protein crystals - Acbas, G.; Niessen, K. A.; George, D. K.; Snell, E.; Markelz, A. G. (Ultrafast Phenomena and Nanophotonics Xvii, 2013)
Using Terahertz near field microscopy we find orientation dependent narrow band absorption features for lysozyme crystals. Here we discuss identification of protein collective modes associated with the observed features. Using normal mode calculations we find good agreement with several of the measured features, suggesting that the modes arise from internal molecular motions and not crystal phonons. Such internal modes have been associated with protein function.
ISI Document Delivery No.: BGG42 Times Cited: 0 Cited Reference Count: 5 Cited References: Bahar I, 2005, CURR OPIN STRUC BIOL, V15, P586, DOI 10.1016/j.sbi.2005.08.007 BROOKS B, 1985, P NATL ACAD SCI USA, V82, P4995, DOI 10.1073/pnas.82.15.4995 BROOKS BR, 1983, J COMPUT CHEM, V4, P187, DOI 10.1002/jcc.540040211 Karplus M, 2005, P NATL ACAD SCI USA, V102, P6679, DOI 10.1073/pnas.0408930102 Planken PCM, 2011, J INFRARED MILLIM TE, V32, P975, DOI 10.1007/s10762-011-9824-3 Acbas, Gheorghe Niessen, Katherine A. George, Deepu K. Snell, Edward Markelz, A. G. Proceedings Paper Conference on Ultrafast Phenomena and Nanophotonics XVII Feb 03-06, 2013 San Francisco, CA SPIE, Femtolasers Inc Snell, Edward/G-2055-2018; George, Deepu/J-9882-2014 Snell, Edward/0000-0001-8714-3191; George, Deepu/0000-0003-0021-0705; Markelz, Andrea/0000-0003-0443-4319 National Science Foundation MRI2 [DBI2959989] We thank the National Science Foundation MRI2 grant DBI2959989 for support. 1000 20th st, po box 10, bellingham, wa 98227-0010 usa 0277-786x 862305
Keywords: correlated motions; dynamics; mode; molecular crystals; molecular vibrations; normal modes; phonons; protein dynamics; spectroscopy; Terahertz

Multi-component response in multilayer graphene revealed through terahertz and infrared magneto-spectroscopy - Ellis, C. T.; Stier, A. V.; George, D. K.; Tischler, J. G.; Glaser, E. R.; Myers-Ward, R. L.; Tedesco, J. L.; Eddy, C. R.; Gaskill, D. K.; Markelz, A. G.; Cerne, J. (37th International Conference on Infrared, Millimeter, and Terahertz Waves, 2012)